Analysis of Factors that Influence the Interest of Accounting Students Following Accounting Professional Education - Rosyadi, Rozi Irfan; Sari, Shinta Permata (Universitas Muhammadiyah Surakarta, 2018)
This study aims to analyze the factors that influence the interest of accounting students to participate in Accounting Professional Education (PPAk) at Universitas Muhammadiyah Surakarta (UMS) and Universitas Sebelas Maret Surakarta (UNS). There are seven factors tested in this study: social motivation, career motivation, economic motivation, bachelor degree motivation, motivation to seek knowledge, quality motivation and education costs. The population in this study are undergradute accounting students in 2015-2016 of accounting departement at UMS and UNS. The sample collection method uses convenience sampling technique. Data collected by giving questioner to 286 respondents. The results of this study indicate that economic motivation, career motivation and social motivation affect the accounting students’ attitudes to follow PPAk. While bachelor degree motivation, motivation to seek knowledge, quality motivation, and education costs have no significant effect on the interests of accounting students following the PPAk.